GRANULAR CELL TUMOR OF THE BREAST: CASE REPORT - Souza, Juliana da Costa; Lima, Juliana Ferreira de; Pace, Aline Bortolotto Di; Prior, Sandro Luiz Sayão; Gebrim, Luiz Henrique (Mastology, 2020)
Introduction: Granular cell tumor (GCT) is rare, usually benign, with less than a 2% chance of malignancy. It is usually located in the tongue, and affects the breast in only 6% of the reported cases, with incidence of 1:1000 cases of breast carcinoma. Its origin is related to the Schwann cells. It presents itself as a firm, painless, moveable mass, smaller than 3 cm. It can affect men and women in several age groups, and is more frequent among black women, from the 4th to the 6th decades of life. The image mimics malignant lesions. Mammography shows: dense, circumscribed, sometimes spiculated nodules, without associated microcalcifications. The ultrasound showed: solid, hypoechoic, heterogeneous, round, irregular nodule, with irregular halo in some cases. Histologically, there are large, polygonal cells, with eosinophilic, granular cytoplasm displayed in blades or trabeculae, with benign, atypical and malignant variants. Positive immunohistochemical (IHC) for markers such as: S00 protein, vimentin, neuron-specific enolase, CD-57, CF-68, inhibin alpha, SOX-10, calretinin, PGP9.5, Gap43. The treatment is the excision of the lesion with margins, with low risk of recurrence. Objective: To describe a case of GCT in Hospital Pérola Byington in January/2019. Method: Cross-sectional, descriptive case report obtained through a medical chart review. Results: S.R.P, 56-year old female, white patient, assisted in January, 2019, complaining of a nodule in the right breast for three months. She denies comorbidities, is not aware of family history of cancer. G1P1N, menacme from the age of 13 to 53, denies hormone therapies. At the first examination: nodule measuring 2.5x2.5cm, in the right SLQ, retracting the nipple; right axilla (RA) showing palpable lymph node. Mammography shows a nodule in the right breast (RB), with irregular shape, partially defined borders, measuring 3.8 cm, located in SLQ(B4)-. An ultrasound guided nodule core biopsy at 10hMD, measuring 2.24x1.52x1.97, RA without findings. Biopsy suggests GCT (without IHC). The choice was to perform an ultrasound guided mammotome with IHC, confirming the GCT (positive for S-100, CD-68, eno-lase and vimentin), submitted to sectorectomy for the excision of the residual lesion. Conclusions: GCT is rare, benign, in most cases; however, when clinical, epidemiological and imaging characteristics suggest cancer, it is necessary to make an anatomopathological confirmation with IHC and excision of the lesion